Tongqiaohuoxue decoction ameliorates obesity-induced inflammation and the prothrombotic state by regulating adiponectin and plasminogen activator inhibitor-1. (4th November 2016) - Kim, Soon-Hee; Park, Hee-Sook; Hong, Moon Ju; Yoo, Ji Young; Lee, Hoyoung; Lee, Ju Ah; Hur, Jinyoung; Kwon, Dae Young; Kim, Myung-Sunny
Abstract: Ethnopharmacological relevance: Tongqiaohuoxue decoction (THD), a water extract of a mixture of eight species of medicinal herbs, has been used for the treatment of blood stasis and hypercoagulation in traditional East Asian medicine since 18th century. Aim of the study: To investigate the in vivo efficacy of THD using high-fat diet (HFD)-induced obese mice with chronic inflammation and a prothrombotic state as an early vascular model. Materials and methods: THD was prepared by hot water extraction and freeze-drying. Male C57BL/6 mice were divided into three groups. Group 1 (NC) mice were fed normal chow. Mice in group 2 (HFD) and 3 (HFD+THD) were fed with HFD for 12 weeks. In addition, Group 3 mice were administered with 100 mg/kg body weight THD for 4 weeks after onset of obesity by HFD for 8 weeks. Glucose tolerance tests and histological tissue examinations were performed. The levels of adipokines, inflammatory markers, and prothrombotic markers were assessed. Results: The oral administration of THD for 4 weeks had no effect on the liver, adipose tissue, or total body weight when the HFD and HFD+THD groups were compared. Nevertheless, mice treated in THD interestingly showed a significant increase in adiponectin in blood and adipose tissue. To verify the effect of THD on adiponectin, 3T3-L1 adipocytes were treated with THD; it stimulated adiponectin production in a dose-dependent manner. In the HFD+THD group, pro-inflammatory cytokines were significantly down-regulated in the blood, adipose tissue, and liver. Insulin resistance was also notably improved by THD. Simultaneously, THD significantly reduced plasminogen activator inhibitor-1 (PAI-1) levels in serum, adipose tissue, and liver. Fibrin deposition and tPA activity, downstream targets of PAI-1, were also notably reduced in the HFD+THD group compared to the HFD group. Conclusions: THD improved obesity-induced inflammation and insulin resistance by increasing adiponectin production. Additionally, THD administration exerted an anti-thrombotic effect through the regulation of PAI-1 and fibrinolysis. This study demonstrates the efficacy of a traditional East Asian medicine by providing scientific evidence and suggesting a possible mechanism of action. Graphical abstract: